Screening of iron deficiency anaemia in early childhood - Sophie Jullien (BMC, 2021)
Abstract We looked at existing recommendations and supporting evidence on the effectiveness of universal screening of iron deficiency anaemia (IDA) in children under five years of age for improving growth, cognitive function, and psychomotor development. We assessed the accuracy of the screening tests for detecting IDA, the efficacy of existing treatment for children with IDA, and the potential harms associated with screening and treatment. We conducted a literature search up to the 18th of August 2019 by using key terms and manual search in selected sources. We summarized the recommendations and the strength of the recommendation when and as reported by the authors. We summarized the main findings of systematic reviews with the certainty of the evidence as reported. There is no suitable test for IDA screening that is non-invasive with high accuracy for detecting IDA and there is uncertainty whether IDA in children causes cognitive and psychomotor delays. There is a lack of evidence on the effects of routine screening for IDA in asymptomatic children under five years of age on growth, cognitive and psychomotor development outcomes. Universal screening of IDA in children under five years of age is not recommended by most organisations such as the Spanish Association of Primary Care Paediatrics, the United Kingdom National Screening Committee, and the United States Preventive Services Task Force, but is recommended by the American Academy of Paediatrics. However, selective screening of IDA is recommended in infants and children with risk factors including prematurity, low birth weight, and dietary risk factors.